Erratum: HENG PAN, YI WANG, GANG TAO & ZHI-YUAN ZHANG (2025) Morphological and phylogenetic characterisation of Podospora sichuanensis sp. nov. (Podosporaceae, Sordariales). Phytotaxa 695 (1): 123–130. - Pan, Heng; Wang, Yi; Tao, Gang; Zhang, Zhiyuan (Phytotaxa, 2025)
N/A